2012
DOI: 10.1016/j.eswa.2012.02.143
|View full text |Cite
|
Sign up to set email alerts
|

Inverse kinematics of a 6 DoF human upper limb using ANFIS and ANN for anticipatory actuation in ADL-based physical Neurorehabilitation

Abstract: Objective: This research is focused in the creation and validation of a solution to the inverse kinematics problem for a 6 degrees of freedom human upper limb. This system is intended to work within a realtime dysfunctional motion prediction system that allows anticipatory actuation in physical Neurorehabilitation under the assisted-as-needed paradigm. For this purpose, a multilayer perceptron-based and an ANFIS-based solution to the inverse kinematics problem are evaluated. Materials and methods: Both the mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…The normalized firing strengths are calculated from the fixed circular nodes in layer 3 as given in (7) and then multiplied with (7) the linear parametric equations (formed in terms of the inputs) in the adaptive square nodes of layer 4, see (8). (8) where are the consequent parameters.…”
Section: The Anfis Architecturementioning
confidence: 99%
See 2 more Smart Citations
“…The normalized firing strengths are calculated from the fixed circular nodes in layer 3 as given in (7) and then multiplied with (7) the linear parametric equations (formed in terms of the inputs) in the adaptive square nodes of layer 4, see (8). (8) where are the consequent parameters.…”
Section: The Anfis Architecturementioning
confidence: 99%
“…Furthermore, finding a closed form solution has been particularly difficult, and even if exist, the solution may not be unique [3][4][5][6] due to the many possible robot configurations for a given end-effector position and orientation. Although several conventional methods namely the algebraic, geometric, and numeric approaches have been adopted to solve the inverse kinematics problem [5], they are still faced with the above mentioned limitations, and the solutions proffered, as in the case of the numeric approach, may be impractical for real time application [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For these methods, the IK problem is addressed as an optimization and the heuristics is used as computing alternatives. The second class includes nature inspired techniques and hybrid techniques with learning capacities such as neural networks and neuro-fuzzy systems (Rutkowski et al, 2012;Juang, 2000;Zaidi et al, 2012;Pérez-Rodríguez et al, 2012) where the IK solver is observed as system with a set of inputs and output(s), the system needs first to be trained using a set of targets and solutions generally obtained using the forward kinematic model, it is then validated with a separate validation set and finally used. When the target point is far from the training set this systems generate limited precision solutions compared to Jacobian based conventional methods (Chiaverini et al, 1994;Buss, 2004); they are also time consuming and can not satisfy real time constraints (Zaidi et al, 2013;Pérez-Rodríguez et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The training process has a direct impact on the quality of the obtained IK solver, for these intelligent IK solvers designing a good training set is essential. Neuro-fuzzy has the advantage to be interpretable when compared to neuralnetwork IK solutions; they are accurate but suffer from computing time, and could not be used in real time applications (Pérez-Rodríguez et al, 2012, Tolani et al, 2000.…”
Section: Introductionmentioning
confidence: 99%